Nestin Reporter Transgene Labels Multiple Central Nervous System Precursor Cells - Avery S. Walker; Gwendolyn E. Goings; Yongsoo Kim; Richard J. Miller; Anjen Chenn; Francis G. Szele (Neural Plasticity)
Embryonic neuroepithelia and adult subventricular zone (SVZ) stem and progenitor cells express nestin. We characterized a transgenic line that expresses enhanced green fluorescent protein (eGFP) specified to neural tissue by the second intronic enhancer of the nestin promoter that had several novel features. During embryogenesis, the dorsal telencephalon contained many and the ventral telencephalon few eGFP+ cells. eGFP+ cells were found in postnatal and adult neurogenic regions. eGFP+ cells in the SVZ expressed multiple phenotype markers, glial fibrillary acidic protein, Dlx, and neuroblast-specific molecules suggesting the transgene is expressed through the lineage. eGFP+ cell numbers increased in the SVZ after cortical injury, suggesting this line will be useful in probing postinjury neurogenesis. In non-neurogenic regions, eGFP was strongly expressed in oligodendrocyte progenitors, but not in astrocytes, even when they were reactive. This eGFP+ mouse will facilitate studies of proliferative neuroepithelia and adult neurogenesis, as well as of parenchymal oligodendrocytes.